Reinterpretasi Nilai Adab dan Etika Kitab Ta‘Lim Al-Muta‘Allim Terhadap Fenomena Feodalisme dalam Pendidikan Pesantren - Yoga Mahath Pandika; Zaini Fasya (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This article aims to reinterpret the concept of adab in Ta‘lim al-Muta‘allim by Burhān al-Dīn al-Zarnūjī in order to clearly distinguish between the ethical values of Islamic education and practices of symbolic feudalism within pesantren education. This study employs a qualitative approach through a literature review of classical texts, Islamic educational studies, and sociological literature on education. The analysis is conducted through a normative reading of the concept of adab in Ta‘lim al-Muta‘allim, combined with a critical interpretation of contemporary pesantren educational practices. The findings indicate that adab in al-Zarnūjī’s thought constitutes a pedagogical ethic that regulates learning orientation, evidentially grounded rationality, ethical relations between teachers and students, self-discipline, and the formation of a conducive educational social environment. The concept of adab is not intended to negate critical reasoning, but rather to cultivate intellectual and moral responsibility among seekers of knowledge. Feudalism in pesantren education is understood as a sociological ph,enomenon arising from charismatic authority structures and symbolic domination, rather than as a direct consequence of normative Islamic teachings. The distortion of adab emerges when its ethical values are reduced to absolute obedience without space for dialogue and critical reflection. Reinterpreting adab as an emancipatory ethic is therefore essential to restoring the function of pesantren education as a space for forming knowledgeable, ethical, critical, and morally responsible individuals.